Letter from Caitlín Brugha, neé Kingston, to Edmund Downey, regarding his article about the Waterford Branch of the "I.D.A.", and news about her printing business - Brugha, Caitlín, 1879-1959; Downey, Edmund, 1856-1937 (1927)
Writes "It is very extraordinary to find that printing orders of a purely Catholic nature are given to firms controlled by Jews or Freemasons here in Dublin without giving Catholics an opportunity of competing".
Manuscript.
Keywords: Brugha, Caitlín, -- 1879-1959 -- Correspondence; Traynor, Oscar, -- 1886-1963.; Ireland -- History -- 1922-; Ireland -- Politics and government -- 1922-1949